A COMPARATIVE SURVEY OF KNOWLEDGE OF ANTISEPTIC AND DISINFECTANT USE AND EFFECT OF INTERVENTION ON MEDICAL AND SURGICAL STAFF NURSES IN A TERTIARY CARE HOSPITAL - Kanchan, Chattar; Sangeeta, Dabhade; Balasaheb, Ghongane (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was carried out to find the knowledge and awareness of medical and surgical section nurses about the use of antiseptic and disinfectants and the immediate and late impact of an educational intervention like seminar and workshop in the knowledge of nurses. Method: This is a questionnaire-based pre- and post-test cross-sectional study. 200 nurses [100 working in medical wards and 100 working in surgical wards and Operation theatre (O.T.)] were selected using random number sampling method. First a pre-test was given. Then an educational intervention in the form of power point presentation was carried out and post-test was given. One more test was carried out 1 month after post-test to check retention of knowledge by nurses. Result: In both medical and surgical pre-test, most of the questions answered correctly were in below 25% response. While in post-test number of the questions answered correctly was increased and maximum number of number of the questions solved correctly were between 50-75% and 75-100 percent. Individual response in the pre-test both medical and surgical nurses showed that maximum number of nurses have responses between 25-50% and 50-75% while response rate has increased in post-test where maximum number of responses were between 75-100%. Conclusion: Our study suggests that educational intervention has positive impact on the knowledge of nurses. There is a need to carry out such educational interventions periodically which will be helpful for better retention of knowledge by nurses.